Using a multiattribute utility model to assess subjective preferences for three methods of analyzing human decision-making behaviors. - Chen, Chi-Kuang (Philippine Industrial Engineering Journal)
The objective of this study was to examine subjective preferences for three methods of analyzing human decision-making behavior by using a multiattribute utility model (MAU). The three methods are linear regression, process-tracing and multimethod. According to the past literature, multimethod is preferable because it provides complementary analysis and other information. However, no empirical study has yet supported this argument. This study examined the participant's subjective preferences to the three methods, in respect of six attributes. The participant was asked to evaluate the academic reputation of 44 universities based on 10 cues. The results showed that linear regression is the most preferred method. In addition, two common cues were important across the three methods : an academic reputation rank, and the percentage of incoming students who were in the top 10 percent of their high school class.